Polska sowietologia do 1939 roku - Pipes, Richard (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
The paper presents the origins and development of the Polish analyses concerning the tsar’s and Soviet Russia. According to the author, the roots of the Polish interpretations of the Soviet system are inherent in the 19th-century accounts of the tsar’s Russia political system, which were initiated by the German scientist, August von Haxthausen 1792–1866. The Haxthausen’s conviction that Russians had a special disposition to communism was subsequently adopted by the Polish thinkers and writers: Henryk Kamieński, Zygmunt Krasiński, and Franciszek Duchiński. The Polish philosopher Wojciech Dzieduszycki observed in 1908 that an attempt to introduce the socialism could only bring the creation of a bureaucratic system. The majority of the Polish witnesses and observers of the rise of the communist regime in Russia after 1917 Jan Kucharzewski, Roman Dmowski, Marian Zdziechowski and Jan Parandowski, among others were of the opinion that the communist system was a continuation of the tsarist one. Władysław Leopold Jaworski fi rmly emphasized, however, that the socialism in the Marx’s version was alien to the Russian culture. In the author’s opinion many Polish commentators of the Soviet Russia e.g. Marian Zdziechowski, Jan Parandowski and Feliks Koneczny stressed the leading role of Jews in the Soviet system. The Scientific-Research Institute of the Eastern Europe Instytut Naukowo-Badawczy Europy Wschodniej — established in 1930 at the University in Wilno — played a distinct role in the Polish sovietology. Two scholars: Wiktor Sukiennicki and Stanisław Swianiewicz, were the leading figures of the Institute. The publications originated in that Institute were deliberately impartial and contributed to the scientific knowledge on the Soviet system.
Keywords: Russia; interpretation; Scientific-Research Institute of the Eastern Europe; Poland